THE PSYCHOPHYSIOLOGICAL EFFECTS OF LISTENING TO ASYNCHRONOUS MUSIC BY DIFFERENT MUSICAL TEMPO DURING ROPE JUMPING EXERCISE - Somnil, Poosanapas; Rachadech, Wanitcha; Yarsiasat, Jiradech; Phochaisri, Phuwadol; Madeu, Thepsanarit; Sriring, Thanaphon (Academic Journal of Thailand National Sports University, 2024)
The objective of this study was to examine and compare the psychophysiological effects of listening to asynchronous music by different musical tempo during jump rope exercise on changes in heart rate, blood pressure, and rating of perceived exertion. Study design was a randomized, single-blind, 3x3 controlled crossover study. The subjects were randomly divided into 3 groups; listening to fast tempo music group (n = 15), listening to slow tempo music group (n = 15) and no music during jump rope exercise group (n = 15). The subjects were served music or no music to listen during jump rope exercise. Heart rate, blood pressure, and rating of perceived exertion were taken before and at the after jump rope exercise immediately. The resulted show that the mean and standard deviation on changes in heart rate, blood pressure, and rating of perceived exertion compare before and at the after exercise immediately between groups; listening to fast tempo music group, listening to slow tempo music group and no music during jump rope exercise group showed no differences and within groups showed differences except for the diastolic blood pressure variable of the group listening to fast tempo music that is no different. A mixed research study may help to understand in the difference between listening to music asynchronously and synchronously by different music rhythms and individual musical preferences.